Yield and Economic Response of Modern Cotton Cultivars to Nitrogen Fertilizer - Irish Lorraine B. Pabuayon (MDPI AG, 2021)
Non-optimal application of nitrogen (N) fertilizer in cotton (Gossypium hirsutum L.) production systems often results from a producer’s uncertainty in predicting the N rate that ensures maximum economic return. Residual soil nitrate-N (NO3-N) is also often unaccounted for in fertilizer management decisions. In this study, the lint yield and profitability of two cotton cultivars (FiberMax FM 958 and Deltapine DP 1646 B2XF) were compared across five N fertilizer treatments [0 kg ha−1 (control), 45 kg ha−1 (N-45), 90 kg ha−1 (N-90), 135 kg ha−1 (N-135), 180 kg ha−1 (N-180)] from 2018 to 2020. For both cultivars, additional N fertilizer on top of the control treatment did not increase the lint yield of cotton. For each year, both control and N-45 treatments resulted in the greatest revenue above variable costs (RAVC) values for all cultivars. The improved N partitioning efficiency in newer cultivars and the high levels of residual soil NO3-N allowed sustained plant growth and yield even with reduced N application. Overall, the results show the advantage of reducing N inputs in residual N-rich soils to maintain yield and increase profits. These findings are important in promoting more sustainable agricultural systems through reduced chemical inputs and maintained soil health.